A new process for enhancing conversion of methyl vinyl ether to propylene yields with Al2O3 hollow spheres. Issue 11 (21st January 2016) - Wang, Yang; Zhang, Wenyu; Zha, Daoan; Hu, Jiaji; Li, Wei; Duan, Wubiao; Liu, Bo
Abstract : The proposed mechanism for a new process to convert methyl vinyl ether to propylene. Abstract : Al2 O3 hollow spheres were successfully synthesized via a simple template method and used to catalyze a new process from methyl vinyl ether to propylene. In this study, it not only indicated that a two-step integration process from acetylene and methanol to propylene is feasible but the prepared catalyst could also adjust the distribution of the products. First, colloidal carbon spheres were formed by the hydrothermal synthesis method, and then the template was used to prepare hollow spheres of Al2 O3 . EDS, XRD, SEM, and TEM all showed that the catalyst was composed of only O and Al and the structures were hollow spheres. In the new process tests, the low carbon olefins are detected as the main products, alkanes are nearly not observed. The participation of Al2 O3 hollow spheres could significantly enhance the selectivity of olefins especially for propylene compared to the results without catalysts. Furthermore, the effects of temperature on the products were also investigated, and a possible radical-involved reaction mechanism is discussed in detail at the end.